How Does the Corporate Culture Affect the Implementation of IFRS? - Yürekli, Emin (International Journal of Contemporary Economics and Administrative Sciences, 2017)
The global economy nowadays is characterized by the sharing of economic influences and results between the countries. The process of globalization is characterized by the fact that the companies are no longer national but multinational with working operations in many countries. The increase of the international trade, the companies’ operations in many countries, the free movement of the capital, goods and services are the lead factors for the need of consistency among the economies and companies worldwide. The differences between the countries related to different culture and attitudes, different regulations, had eventually led to the need for many types of harmonization in the global economy. On the other hand, the global market requirements for presentation of consistent financial results for the companies’ performance has increased as the process of globalization had become more intensive. The capital investors have huge requirements for financial information which need to be comparable and summarized in the financial statements. Moreover, the need for consistent presentation of financial information has contributed development of IFRS’s and other GAAP’s. This study examines the correlation between the use of IFRS’s and the corporate culture adopted by the companies. The results of this study confirmed that the cultural dimensions such as goal oriented company, externally oriented companies, those which follow easy-going working practice have adopted IFRS so far.